Mesclas entre livro didático, experimento real e experimento virtual no ensino e aprendizagem de Física no ensino médio - Rubert, Crístian da Costa (2014)
The main objective of this research was to plan, implement and analyze the teaching and learning of physical activities, aiming to blend three kinds of teaching resource (Textbook, Real Experiment and Virtual Experiment - Simulator), for the same activity. In this context, the research problem sought to examine whether the merged utilization of these resources enhances the understanding of physical concepts developed during the activities. The development of the research took place in a class of high school at an institute in central Santa Maria, RS. The chosen methodology was action research, so are the inclusion of the researcher community to be analyzed and features moments of action, observation, reflection and redesign. The results from the analysis of data collected through survey questionnaires, diaries lips and students' responses in the proposed work, indicate that there are points of similarity between the merged teaching resources and it was concluded that these worsened the understanding of physics concepts by students.